Can Federalism Save India's Constitutional Democracy? - Sujit Choudhry (Jus Cogens, 2022)
Madhav Khosla's brilliant book, India's Founding Moment , is self-consciously a work on the history of ideas.~Nonetheless, the subtitle of India's Founding Moment — The Constitution of a Most Surprising Democracy —implies that Khosla draws a connection between the ideas that shaped the creation of constitutional democracy in India and its endurance. In this review, I pose the question of whether the design of the Constitution can be a source of constitutional resilience against the rising threat of authoritarianism and Hindu majoritarianism.
Keywords: 330; India; Constitution; Federalism; Political party